2014
DOI: 10.1177/1540796914534633
|View full text |Cite
|
Sign up to set email alerts
|

Does Providing Transition Services by Age 14 Produce Better Vocational Outcomes for Students With Intellectual Disability?

Abstract: This study examined the potential impact providing transition services early had on the vocational outcomes achieved by young adults with intellectual disability. Two groups were compared: 7,520 individuals from states requiring transition services be addressed in individualized educational programs (IEPs) by age 14 and 7,520 individuals from states requiring transition services be addressed by age 16. Individual from both groups were matched based on seven demographic variables. Results found that, in each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…59.6% of sheltered workshop supported employees were competitively employed compared to 60.4% for individuals who did not participate in shetered workshops prior to entering supported employment. This difference was not statistically significantCimera et al [49], USACohort study. Matched pairs 2006–2009.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…59.6% of sheltered workshop supported employees were competitively employed compared to 60.4% for individuals who did not participate in shetered workshops prior to entering supported employment. This difference was not statistically significantCimera et al [49], USACohort study. Matched pairs 2006–2009.…”
Section: Resultsmentioning
confidence: 86%
“…Two studies [51, 59] did not report the gender of the participants. Seven studies reported the ethnicity of the participants [45, 4749, 51, 52, 79].…”
Section: Resultsmentioning
confidence: 99%
“…These negative outcomes are due to several barriers, including a lack of guidance on how to achieve goals, negative parent-professional relationships, a lack of knowledge of available services and support, low expectations and discrimination (Francis et al, 2014;US GAO, 2012). However, effective transition planning as young adults prepare to exit educational systems can address these common barriers and improve post-school outcomes (Cimera et al, 2014). Similar to educational policies outside the US (for example, Special Education Needs and Disability Code of Practice: 0 to 25 years, UK Department for Education and Department of Health and Social Care, 2015; United Nations Convention on the Rights of Persons with Disabilities, UN, 2006), in the US, the Individuals with Disabilities Education Act (IDEA, 2004) requires that adolescents with disabilities receive appropriate services to successfully transition out of secondary school.…”
mentioning
confidence: 99%
“…These negative outcomes are due to several barriers, including a lack of guidance on how to achieve goals, negative parent-professional relationships, a lack of knowledge of available services and support, low expectations and discrimination (Francis et al, 2014;US GAO, 2012). However, effective transition planning as young adults prepare to exit educational systems can address these common barriers and improve post-school outcomes (Cimera et al, 2014).…”
mentioning
confidence: 99%
“…The provision of transition services to children by age 14 produces better vocational outcomes for young adults with ID. Cimera, Burgess and Bedesen [39] compared two groups of states requiring transition services be addressed in individualized educational programs by age 14 and by age 16. The study results indicated that in states where transition services were provided early, by age 14, individuals were more likely to be employed by the time their cases were closed, compared to their peers in states where transition services were provided later, at age 16.…”
Section: Theme Two: Key Objectives Of Transition Servicesmentioning
confidence: 99%